1986
DOI: 10.1247/csf.11.9
|View full text |Cite
|
Sign up to set email alerts
|

Population-dependent requirements of vitamin B12 and metabolically related substances of several mouse cell types in serum-free, albumin-fortified medium.

Abstract: ABSTRACT.Mouse FM3A cells propagated well in serum-free medium containing 0.5 % serum albumin and 1ƒÊg of insulin/ml. The vitamin B12 (B12)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…They explained that these metabolites, which the cells could synthesize in amount sufficient for sustained growth, but which at low population densities were lost from the cell to the environment in amount which exceeded the biosynthetic capacity of cells. Matsuya et al in 1986 also reported that the vitamin B 12 requirement of mouse FM3A cells was dependent on the population density [12]. The maximum viable cell number and integral of the number of viable cells over culture time were influenced by the serum concentration and the initial cell densities.…”
Section: Cell Culturesmentioning
confidence: 97%
“…They explained that these metabolites, which the cells could synthesize in amount sufficient for sustained growth, but which at low population densities were lost from the cell to the environment in amount which exceeded the biosynthetic capacity of cells. Matsuya et al in 1986 also reported that the vitamin B 12 requirement of mouse FM3A cells was dependent on the population density [12]. The maximum viable cell number and integral of the number of viable cells over culture time were influenced by the serum concentration and the initial cell densities.…”
Section: Cell Culturesmentioning
confidence: 97%